Webinar Pengabdian: Meningkatkan Kreativitas Seni Siswa SD di Masa Pandemi melalui Pemanfaatan Barang Bekas di Rumah - Aisyah Herlina Arrum; Adella Yutikawati; Fadel Daulatullail; Mufidah Mufidah; Syifa Aulia Nurul Uula; Tiara Nurul Syamsiah; Erna Suwangsih; Rina Nurhayati Setiani (Universitas Pendidikan Indonesia Kampus Serang, 2021)
The implementation of online learning during this pandemic has a huge impact on the sector of education, one of those is the implementation of education at UPTD SDN 1 Munjuljaya which is identical to its musical activities. The learning process which carried out by online, especially in practicing the art activities is very difficult to do because it requires practice directly, so it causes the art creativity of students can’t be optimally developed considering the increasing spread of the covid-19 virus. One of the things that can overcome this problem is we carried out a community service through webinar with the theme “Improving Elementary School Students Art Creativity during the Pandemic through Utilizing Secondhnd Goods at Home”. The method that used id an online webinar via Zoom Meeting platform which is attended by 70 participants including students in grade 3, 4, 5, and 6. Through this webinar, the students are very enthutiastic in developing art creativity by utilizing secondhand goods at home although this activity carried out online. In this webinar, the students practice a beat by following the instructions of the speaker, they are also assigned to make a work, so its helps students to increase their creativity in using second-hand goods